Occupational therapy students' perception of the methodologies used in the subject collective creative processes - Ortuzar Acevedo, Natalia; Ilabaca, Jessica; Henríquez Hurtubia, Camila (Relatos Journal, 2025)
The training of Occupational Therapists varies across several paradigms, primarily mediated by the university that offers the program, thus determining diverse graduate profiles.At Andrés Bello University, in the Occupational Therapy program, we find methodologies used to guide instructors in their training of students, such as active methodologies. These respond to the idea of ​​placing the student at the center of learning, where the instructor plays a facilitating role in the teaching and learning process.This research presents the perceptions of Occupational Therapy students at Andrés Bello University, Viña del Mar, regarding the use of active methodologies in the Collective Creative Processes (CCP) course taught in the second year of the program. The overall objective is to evaluate the impact on the Occupational Therapy Students (OTS) of active teaching methodologies applied in the PCC course at the School of TO at UNAB Viña del Mar.To this end, a mixed-methods research study was conducted, using a Likert-scale questionnaire as a data collection instrument, with four assessment criteria and 10 closed-ended questions: strongly agree, somewhat agree, partially agree, disagree, and two open-ended questions.It is relevant to the subject to gather this information and to make visible, through students' perceptions, how these types of methodologies facilitate their teaching and learning processes, promoting the integration of knowledge through bodily and emotional experience.
Keywords: Occupational Therapy; Occupational Therapy training; Active Methodologies